Design, characterization of Resveratrol-Thermosensitive Hydrogel System (Res-THS) and evaluation of its anti-depressant effect via intranasal administration - Jin-Feng Zhou; LiLi Duan; Yu-Xin Wang; Chen-Lin Wang; Meng-Li Tian; Xue-Jie Qi; Feng Qiu (Materials & Design, 2022)
Thermosensitive Hydrogel System (THS) is a suitable candidate for targeted drug delivery, because of its intelligent response and controlled release. In this work, combination of guanidine-chitosan (GCS), β-glycerol phosphate disodium salt (β-GP) and hydroxypropyl-β-cyclodextrin (HP-β-CD) can successfully result in a novel THS by single factor and response surface method. The characterization of THS is detected with gelation temperature, FT-IR, SEM, in vitro release, rheology and biocompatibility. Resveratrol (Res) is selected as a model drug to evaluate the anti-depressant effects of THS loaded Res (Res-THS) via intranasal administration of chronic unpredictable mild stress (CUMS) rats. The results display that the Res-THS can increase concentration of neurotransmitter in rats’ brain tissue via intranasal administration, indicating the anti-depressant effect.